MENJAGA NILAI, MENYEMAI KEPARIWISATAAN GLOBAL YANG BERKEKUATAN LOKAL - Nurmansyah, M. Andhy; Prawoto, Sigit; Hapsari, Dyah Eko; Rusmawati, Roosi; Khasanah, Ismatul (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2020)
The development of Kampung Biru Arema (KBA) to become an educational tourist destination in urban areas is a necessity to support an increase in the community's economy. Development carried out independently has not shown optimal results so that it requires the intervention of various parties to support in realizing the aspirations of the community. The academic community of the Faculty of Cultural Sciences as part of its academic responsibilities takes part in developing the village in the form of community assistance. This community service program is intended to provide assistance to the KBA community to become an integrated educational tourist destination. After conducting a series of preliminary activities, an agreement was reached to develop five (5) tourist points to be further developed as the main sites for KBA tourism activities. The five points were named Tourism Areas: History, Dolanan, Disaster Mitigation, Arema, and Basa Walikan. The stakeholders involved in this program have shown seriousness in the effort to realize the ideal picture of the direction and form of the KBA and committed to carry out development as planned together in the next phase. For this reason, the community service team embodies the shared understanding in a tangible form in the form of visual designs, physical structure in the form of miniature areas developed in tourist areas. In addition, the team also constructed an area at the KBA tourist location as a model for the realization of the visual design.